Downregulation of a novel long noncoding RNA TRPM2-AS promotes apoptosis in non–small cell lung cancer - Cheng Huang; Yingzhi Qin; Hongsheng Liu; Naixin Liang; Yeye Chen; Dongjie Ma; Zhijun Han; Xiaohui Xu; Xiaoyun Zhou; Jia He; Shanqing Li (Tumor Biology)
Non–small cell lung cancer is one of the most common types of cancer, and the prognosis of non–small cell lung cancer is still poor. Recent evidence has proved that long noncoding RNA is involved in tumorigenesis. For non–small cell lung cancer, the expression profile of long noncoding RNA has been studied. Here, we identified a novel long noncoding RNA TRPM2-AS from published dataset and found TRPM2-AS is widely upregulated in non–small cell lung cancer tissues compared with adjacent non-tumor tissues. Higher expression level of TRPM2-AS was correlated with higher TNM stages and larger tumor size. Patients with high TRPM2-AS expression level had poor survival than those with low TRPM2-AS level. We silenced TRPM2-AS by small interfering RNA and found that cell proliferation was significantly inhibited after knockdown of TRPM2-AS. Annexin V/propidium iodide staining and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling assay confirmed that cell apoptosis increased after TRPM2-AS knockdown. Further experiments showed that silence of TRPM2-AS upregulated SHC1 and silence of SHC1 partially reversed cell apoptosis after TRPM2-AS knockdown. In summary, the novel long noncoding RNA TRPM2-AS upregulated in non–small cell lung cancer, and downregulation of TRPM2-AS promotes apoptosis in vitro.